Integração entre polícia e comunidade na prevenção da violência: desafios e possibilidades para a segurança pública no estado do Pará - José Ronilson Nogueira Chaves (Revista ft, 2026)
Violence prevention has increasingly required public security models that go beyond exclusively reactive practices and value strategies of proximity, social participation, and institutional cooperation. In this context, integration between police and community has emerged as a relevant axis for building more legitimate, preventive, and territorially sensitive responses. This article aimed to analyze, based on a literature review, the contributions of police-community integration to violence prevention, highlighting challenges and possibilities for public security in the State of Pará. Methodologically, this is a bibliographic review study with a qualitative approach and a descriptive-analytical character, based on five scientific articles published between 2022 and 2025, focused on community policing, security governance, and citizen participation. The results indicate that integration between police forces and the population favors the construction of trust, expands the circulation of information in the territory, strengthens preventive practices, and contributes to responses better adjusted to local violence dynamics. It was also found that the effectiveness of this model depends on factors such as institutional continuity, professional training, state leadership, civic engagement, and coordination among multiple actors. It is concluded that violence prevention in Pará can be strengthened by public security policies based on proximity, co-production of order, and integrated territorial governance.